Mobile Game Price Discrimination effect on users of Freemium services– An initial outline of Game of Chance elements in Japanese F2P mobile games - Marco Koeder; Ema Tanaka; Philip Sugai (International Telecommunications Society (ITS), 2017)
This paper offers a look at the Japanese mobile free to play market with a focus on “Gacha”, a game of luck mechanism used in many Japanese games. The paper tries to explain about the concept of Gacha, its different forms, some known regulation issues and briefly looks at player and professional's insights and discusses an analytical framework for further studies to figure out the reason of player's acceptance of price discrimination in F2P mobile games.
Keywords: 330; Free-to-play; freemium; mobile games; lottery; behavior; attitudes; virtual goods; Japan